A service science framework for improving innovation processes in manufacturing companies. Comparative case study between a food industry and a non-edible agricultural products industry. - Arcos, Claudio; Calvache, Pablo (CONECTIVIDAD, 2026)
This article describes a service science approach to improve innovation processes with a case study applied to two industries: food processing and production of non-edible agricultural products. The case study shows a method with its different stages for supply chain identification in the two selected industries and describes its use for identifying innovation projects. Based on a literature review on processes and innovation, a framework for improving innovation processes is proposed. The main contributions of this article consist in proposing a framework to support the decision of new innovation projects in manufacturing companies, exposing lessons that can be useful for managers who want to boost innovation in their manufacturing companies. This framework includes both strategic and operational dimensions to identify some of the key challenges and opportunities in innovation projects